Individual differences in emotion differentiation modulate electrocortical dynamics of cognitive reappraisal. (24th September 2020) - Wang, Yali; Liao, Caizhi; Shangguan, Chenyu; Shang, Wenjing; Zhang, Wenhai
Abstract: Cognitive reappraisal plays an important role in individuals' mental health and adaptation and depends on individual differences in emotion differentiation. However, it is unclear how individual differences in emotion differentiation modulate the electrocortical dynamics of cognitive reappraisal. To this end, we employed event‐related potentials (ERPs) and source analysis to characterize temporal dynamics and cortical functions of cognitive reappraisal related with positive emotion differentiation. The electroencephalogram (EEG) data from 36 participants (aged 18–25 years) were recorded when they were required to view neutral, pleasant emotional stimuli, or positively reappraise neutral emotional stimuli. Results showed that, compared with the individuals with low positive emotion differentiation, the individuals with high positive emotion differentiation presented larger late positive potential (LPP) amplitude enhancement during positive reappraisal. Source analysis further found that individuals with high positive emotion differentiation exhibited more activations in the middle frontal gyrus (Brodmann area [BA] 11), superior temporal gyrus (BA 38), and inferior frontal gurus (BA 47) when they implemented cognitive reappraisal as compared with their counterparts. Our findings deepen our understanding of the dynamic cortical organization of how positive emotion differentiation impacts cognitive reappraisal and informs cognitive reappraisal interventions for individuals with low emotion differentiation. Abstract : Our findings add a new electrophysiological perspective to interpret the association between emotion differentiation and emotion regulation. Although some recent studies have suggested that negative emotion differentiation facilitated emotion regulation, we complement new evidence that positive emotion differentiation can also promote emotion regulation, in demonstrating that it modulates the LPP amplitudes and brain regions of cognitive reappraisal.